Pemanfaatan AI dalam Pendidikan: Meningkatkan Pembelajaran melalui Sistem Pembelajaran Adaptif - Haidar Triari Respati (MERDEKA : Jurnal Ilmiah Multidisiplin, 2024)
Education today faces significant challenges in adapting learning methods to meet the diverse needs of students. Artificial Intelligence (AI) technology emerges as an innovative solution, particularly through adaptive learning systems, which can offer personalized learning experiences. These systems allow for real-time adjustments to learning materials based on students' strengths, weaknesses, and learning pace, enhancing their engagement and motivation. This research aims to evaluate the impact of implementing AI-based adaptive learning systems on students' learning outcomes and their motivation to learn. Additionally, this study explores the challenges faced in its implementation, such as the technological access gap and the readiness of educators to use AI. By employing the Systematic Literature Review (SLR) method, this research analyzes various recent studies on the utilization of AI in education, particularly in adaptive learning systems. The results show that the personalization offered by these systems significantly contributes to the improvement of students' learning outcomes and motivation. However, certain challenges related to data privacy and the technological access gap still require further attention to ensure the benefits of this technology are equitably accessible.